Transformation of Communication of Women’s Movement in the New Media: Seeking Gender Justice in Surakarta and Yogyakarta - Sih Natalia Sukmi (Jurnal Perempuan, 2016)
Violence against women is still a thorny issue in Indonesia. Data of Lembar Fakta Catatan Tahunan (CATAHU) from National Commission for Women in 2015 reached to 16.217 cases. Discrimination of local regulations, religious intolerance, death penalty policy, evictions, and political conflicts are considered associated with it. Resistance to this issue has been conducted through social movements (women), but the results have not been succesful. The development of the women’s movement has shifted from the old social movements (physical) towards new social movements (digital). Advancement in technology of new media communication hasprovide a space for people to interact in a novel patterns. Internet is considered as a medium capable of facilitating the movement of women to communicate their aspirations, mobilizing the masses to make collective actions. This paper aims to describe the transformation of communication through new media in the women’s movement for gender justice with case studies in Surakarta and Yogyakarta. This study is conducted in several groups of the women’s movement which are based in community and NGO.